Richard III - Shakespeare, William 1564-1616.; Loncraine, Richard (United States United Artists, 1995)
An adaptation of Shakespeare's play set in the 1930s civil war.
Also available in widescreen format (VDR-1178).
Playwright: William Shakespeare ; writers: Ian McKellen and Richard Loncraine ; executive producer: Maria Apodiacos ; producer: Stephen Bayly.
Cast: Ian McKellen, Annette Bening, Jim Broadbent, Robert Downey Jr., Nigel Hawthorne, Kristin Scott Thomas, John Wood and Maggie Smith.
Keywords: Richard III -- King of England -- 1452-1485 -- Drama; Feature films